AN INFLUENCE OF AEROBIC ACTIVITIES ON SPECIAL ENDURANCE OF STUDENTS IN GROUPS WITH A SPORTS ORIENTATION (SECTIONAL ACTIVITIES) OF PING-PONG - Vitaliy, Grinko (Indonesian Journal of Learning and Instruction, 2019)
The purpose of this study is experimentally to reveal the influence on the special endurance of aerobic activities (cross training and basic aerobics), which are included in the program of higher educational institutions of groups with sports orientation (sectional classes) Ping-Pong, and to explore the need to include these classes in the curriculum for physical education. The methods use analysis and generalization of literary sources, pedagogical observation, pedagogical experiment, modeling. In the experiment, 106 first-year students took part: 53 is control group and 53 is experimental. The result of this study is technique of revealing the influence of aerobic training on the special endurance of students of groups with a sports orientation is tested; the effectiveness of the experimental technique of training for increasing special endurance was developed and proved. So, it can be concluded that at this stage of the experiment, the effectiveness of the program was substantiated and proved with the inclusion of aerobic activities (cross training and basic aerobic elements) in the training groups on sporting orientation (sectional classes) Ping-Pong.